Using a Community Health Development Framework to Increase Community Capacity: A Multiple Case Study. Issue 1 (January 2017) - Garney, Whitney R.; Wendel, Monica; McLeroy, Kenneth; Alaniz, Angela; Cunningham, George; Castle, Billie; Ingram, Monique; Burdine, James
Abstract : The Physical Activity and Community Engagement Project utilized a comparative case study to understand how a theoretical framework called community health development (CHD) influences community capacity. Three rural communities (cases) developed interventions using a CHD framework. Researchers collected qualitative evidence measuring capacity and the CHD process for more than 3 years. Patterns identified seven capacity constructs relevant to CHD, including community history, civic participation, leadership, skills, resources, social and interorganizational networks, and critical reflection. Community health development focuses on population health improvement and strengthening community capacity. As such, it helps communities address local priorities and equips them to address future issues.